Sando Marteu: il cantore di Lubumbashi - Flavia Aiello; Roberto Gaudioso (Kervan. International Journal of Afro-Asiatic Studies, 2019)
This article stems from a field research carried out in Lubumbashi in September and October 2018, as part of a national project on contemporary RDC, with a focus on the swahilophone creative expressions. It aims at outlining the poetics of the sing-songwriter Sando Marteau as it springs from his texts in Swahili, within the linguistic and cultural context of Lubumbashi.